(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Medicinal plants are emerging issue in global scenario now. The plants are used for various disease conditions from time immemorial before upcoming of modern medicine. Though today modern medicine is capable to control major issues in medical emergencies but leaves certain lacunae due to it’s post management hazardous situations. Several fields are still unattended completely by modern medicines. Interestingly, traditional system of medicine like Ayurveda, Siddha etc., plays a vital role till today in remote areas for managing several medical issues exclusively by using medicinal herbs as a tradition of Ayurveda & Siddha. Both the systems advocate, numerous medicinal plants for various disease conditions. It was the interest to document the medicinal plants used for Reproductive Child Health (RCH) along with Mother and Child Health (MCH) as a small component of great Ayurvedic and Siddha ocean. Usually these medicinal plants have important role in the management of RCH & MCH issues. Such claims of advocating its perspective importance possibly to meet the need by extensive research in future. We do not claim its positive assessment but such prevailing claim are only documented here for future research. Medicinal plants have been presented here with scientific preview in every RCH & MCH issues.